การใช้แนวทางสันติวิธีในการแก้ไขความข้ดแย้ง : ศึกษากรณีโครงการท่อส่งก๊าซและโรงแยกก๊าซ ไทย-มาเลเซีย อำเภอจะนะ จังหวัดสงขลา - จิตราภรณ์ สมยานนทนากุล (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
This thesis aims to study the understanding and the perception of nonviolence among the conflicting parties and to study the conditions impeding the effectiveness of nonviolent conflict resolution. The hypotheses of this thesis are that the perception of nonviolence among the conflicting parties is different, and the nonviolent conflict resolution is impeded by the lack of trust building as well as channels of communication in their approach to conflict resolutions. The study applies qualitative research method using secondary data and in-depth interview of strategic groups including the project company, the supporters, the opponents, government officials and the third party. The finding reveals that, basically, the perception of nonviolence among the conflicting parties has been the same; they have denied resorting to physical violence. However, there are differences in the perception of the types of violence and nonviolence. The differences are in the recognition of structural violence, and the use of nonviolent principle and strategy. The finding also unfolds that there was an effort to build trust but within specific groups. Failure to incorporate the management of distrust in conflict resolution process in both conflicting parties has led to greater prejudices and suspicion of the subsequent actions by the opposite parties. Finally, the finding reveals that there has no direct channel of communication between parties when the conflict became more polarized. The role of third party has been introduced to bridge the communication but still encountered three major problems, namely, the confidence in and the unclear role of the third party. As a result of impaired channels of communication, problems of misunderstanding, misinterpretation and misperception increased, affecting the level of trust, therefore is not conducive to the use of nonviolent conflict resolution.